(untitled) (Revista Desenredo, 2019)
This article aims at investigating texts that approach environmental discourses in textbooks for English language teaching and their implications in education. The data are selected by means of i) gathering of texts in the book collections approved by PNLD 2015; ii) identification of the environmental perspective and its characteristics among the selected texts regarding genre, support, theme, and context of production. The results demonstrate that the rational perspective is predominant among the texts disseminated , the institutional type of support was the leading format and the majority of them came from inner circle sources. As for implications, we emphasize: i) the use of images may promote the opportunity for(critical) literacy fostering the construction of new meanings; ii) the predominant texts from the inner circle sphere distance the student from peripheral perspectives and the English language use as international or so called “língua franca”; iii) the focus on the rational perspective keeps technical or technological actions as the solution for environmental problems.